Dual H2O2‐Amplified Nanofactory for Simultaneous Self‐Enhanced NIR‐II Fluorescence Activation Imaging and Synergistic Tumor Therapy. Issue 37 (13th August 2022) - Zheng, Ziliang; Chen, Xuejiao; Ma, Yanchun; Dai, Rong; Wu, Shutong; Wang, Tong; Xing, Jun; Gao, Jinnan; Zhang, Ruiping
Abstract: Activatable fluorescence imaging in the second near‐infrared window (NIR‐II FL, 1000–1700 nm) is of great significance for accurate tumor diagnosis and targeting therapy. However, the clinical translation of most stimulus‐activated nanoprobes is severely restricted by insufficient tumor response and out‐of‐synchronization theranostic process. Herein, an intelligent nanofactory AUC‐GOx/Cel that possesses the "external supply, internal promotion" dual H2 O2 ‐amplification strategy for homologous activated tumor theranostic is designed. This nanofactory is constructed via a two‐step biomineralization method using Au‐doped Ag2 S as a carrier for glucose oxidase (GOx) and celastrol, followed by the growing of CuS to "turn off" the NIR‐II FL signal. In the overexpressed H2 O2 tumor‐microenvironment, the CuS featuring a responsive‐degradability behavior can effectively release Cu ions, resulting in the "ON" state of NIR‐II FL and Fenton‐like activity. The exposed GOx can realize the intratumoral H2 O2 supply (external supply) via the effective conversion of glucose, and mediating tumor‐starvation therapy; the interaction of celastrol and mitochondria can offer a substantial increase in the endogenous H2 O2 level (internal promotion), thereby significantly promoting the chemodynamic therapy (CDT) efficacy. Meanwhile, the dual H2 O2 ‐enhancement performance will in turn accelerate the degradation of AUC‐GOx/Cel, and achieve a positive feedback mechanism for self‐reinforcing CDT. Abstract : In this work, an intelligent nanofactory (AUC‐GOx/Cel) that utilizes the "external supply, internal promotion" dual‐strategy to amplify intratumoral H2 O2, thereby achieving H2 O2 ‐activated NIR‐II fluorescence‐guided the self‐enhanced chemodynamic and starvation therapy, is designed. The dual H2 O2 ‐amplification strategy is suggested for use in homologous activated tumor theranostics.